A CONCEPTUAL MODEL OF INFORMATION SECURITYSTATE INFORMATION RESOURCES - Юдін, О. К.; Бучик, С. С. (Science-based technologies, 2014)
The analysis of construction of models of safety of informative resources is conducted in the article. The accented attention is on the necessity of including for any model of informative safety of approaches of the General criteria. Built conceptual model of informative safety of state informative resources, exposed her basic components. Shown directions of further researches in relation to the analysis of existing and to the construction for the informative systems which contain the state informative resources of flow diagrams of the systems of information protection.